Deskripsi Singkat Revisi Taksonomi Bloom - Rukmini, Elisabeth (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The Bloom's taxonomy revision mainly consisted of curriculum, instructional design, and assessment. Educational development, sociocultural changes, researches in neurosciences and educational psychology are the major influences those supported the revision. Civitas academia may find that the Revised Bloom's Taxonomy is very helpful in its application. The users would find technical and more applied instructions, including some examples. This article was written to describe briefly of the Revised Bloom's Taxonomy as a stepping point in considering its further application.